A review of the African snake-eyed skinks (Scincidae: Panaspis) from Angola, with the description of a new species - Ceríaco, Luis M. P.; Heinicke, Matthew P.; Parker, Kelly L.; Marques, Mariana P.; Bauer, Aaron M. (Zootaxa, 2020)
The genus Panaspis in Angola is represented by four species, most of them part of taxonomically and nomenclaturally challenging species-complexes. We present a taxonomic revision of the group in the region and describe one new species, Panaspis mocamedensis sp. nov., endemic to the lowland areas of the Namibe province, southwestern Angola. Phylogenetic analysis using a combination of mitochondrial (16S, cytb) and nucleares (RAG1, PDC) markers, as well as morphological and meristic data support the recognition of the new species. In addition, these data support the presence of nominotypical Panaspis cabindae, P. wahlbergi and P. maculicollis in Angola. Reexamination of the Angolan population of P. breviceps was based on morphological analysis, as no molecular data from Angola is available for this species. According to our results, this population likely represents the nominotypical form, but due to its complex taxonomic and nomenclatural history and the lack of molecular data, this population needs to be reconsidered when molecular data become available. The description of a new species and revision of the Angolan Panaspis contributes to a better understanding of the true species richness of the Angolan herpetofauna, as well as to understanding the major biogeographic patterns of the region. A key to Angolan Panaspis species is also presented.